Respuesta :

Answer:

1. Rewriting the expression 5.a.b.b.5.c.a.b.5.b using exponents we get: [tex]\mathbf{5^3a^2b^4c}[/tex]

5.  [tex]x^-6 = \frac{1}{x^6}[/tex]

6. [tex]5^{-3}.3^{-1}=\frac{1}{5^3.3^1}[/tex]

7. [tex]a^{-3}b^0c^4=\frac{c^4}{a^3}[/tex]

Step-by-step explanation:

Question 1:

We need to rewrite the expression using exponents

5.a.b.b.5.c.a.b.5.b

We will first combine the like terms

5.5.5.a.a.b.b.b.b.c

Now, if we have 5.5.5 we can write it in exponent as: [tex]=5^{1+1+1}=5^3[/tex]

a.a as [tex]a^{1+1}=a^2[/tex]

b.b.b.b as: [tex]b^{1+1+1+1}=b^4[/tex]

So, our result will be:

[tex]5^3a^2b^4c[/tex]

Rewriting the expression 5.a.b.b.5.c.a.b.5.b using exponents we get: [tex]\mathbf{5^3a^2b^4c}[/tex]

Question:

Rewrite using positive exponent:

The rule used here will be: [tex]a^{-1}=\frac{1}{a^1}[/tex] which states that if we need to make exponent positive, we will take it to the denominator.

Applying thee above rule for getting the answers:

5) [tex]x^{-6} = \frac{1}{x^6}[/tex]

6) [tex]5^{-3}.3^{-1}=\frac{1}{5^3.3^1}[/tex]

7) [tex]a^{-3}b^0c^4=\frac{b^0c^4}{a^3}[/tex]

We know that [tex]b^0=1[/tex] so, we get

[tex]a^{-3}b^0c^4=\frac{b^0c^4}{a^3}=\frac{c^4}{a^3}[/tex]